Relationship Between Adverse Events Following DPT-HB-HiB Immunization (AEFI) and Maternal Knowledge with Maternal Motivation to DPT-HB-HiB3 Immunization - Wikarya, Rionitara; Rita Aninora, Novia; Permata Sari, Putri (Rifa'Institute, 2025)
Introduction: Preventive efforts in health development is by implementing an immunization program. In Padang City, the coverage of complete basic immunization is at 69.2% and the coverage of DPT-HB-HiB3 immunization is the lowest, namely 66.1%. Objective: the aim of this study was to determine the relationship between adverse events following DPT-HB-HiB immunization and maternal knowledge with maternal motivation for DPT-HB-HiB3 immunization. Method: This study uses a quantative research design with a cross-sectional approach. The study was conducted at the Alai Health Care from January to February 2025. The population in this study were mothers who had children aged 2 to 4 months. The sampling technique used purposive sampling with total 50 people. Data analysis was done univariately and bivariate using the chi square test. Result and Discussion: more than half (66%) respondents were experienced AEFI, more than half (76%) respondents were good knowledge, and more than half (70%) respondents were motivated to DPT-HB-HiB immunization. There, relationship between AEFI and maternal knowledge with maternal motivation to DPT-HB-HiB3. Conclusions: Respondents motivated because of the mother's experience in dealing with AEFI and the mother's knowledge about immunization, so that this knowledge can also motivate mothers to continue providing DPT-HB-HiB3 immunization to their children.